The moderating effect of skills development transfer on organizational commitment - a case-study of Free State TVET colleges - Naong, Tshedi (Problems and Perspectives in Management, 2016)
One of the legacies of Apartheid South Africa which has ominous consequences for the economy, is the insidious dire skills shortage for majority of the citizens. Compelling government to embark on an intensive wholesale skills development to ameliorate and stimulate the general economic performance. This paper therefore, explored the relationship between employee organizational commitment and skills development transfer. A longitudinal study, with a pre- and post-quasi experimental research design was adopted in this paper employing Organizational Climate (OC) instrument to collect data from 59 randomly selected TVET college employees. The study revealed significant correlation between organizational commitment and skills development transfer. For example, appreciative of the access to training opportunities, involvement and frequency of training, sense of belonging, an indicative of the affective organizational commitment, with meagre 23% indicating intention to use acquired new skills to look for greener pastures elsewhere. This paper attempts to assist organizations better tailor their training provision to align it with certain desirable behavioral patterns, so as to enhance organizational commitment and reduce the turnover rate of staff.
Published Article
Keywords: TVET colleges; skills transfer; organizational commitment; staff turnover; performance